B-cell malignancies and COVID-19: a narrative review. (March 2023) - Luque-Paz, David; Sesques, Pierre; Wallet, Florent; Bachy, Emmanuel; Ader, Florence; ,
Abstract: Background: COVID-19 has been extensively characterized in immunocompetent hosts and to a lesser extent in immunocompromised populations. Among the latter, patients treated for B-cell malignancies have immunosuppression generated by B-cell lymphodepletion/aplasia resulting in an increased susceptibility to respiratory virus infections and poor response to vaccination. The consequence is that these patients are likely to develop severe or critical COVID-19. Objectives: To examine the overall impact of COVID-19 in patients treated for a B-cell malignancy or receiving chimeric antigen receptor T (CAR-T) immunotherapy administered in case of relapsed or refractory disease. Sources: We searched in the MEDLINE database to identify relevant studies, trials, reviews, or meta-analyses focusing on SARS-CoV-2 vaccination or COVID-19 management in patients treated for a B-cell malignancy or recipients of CAR-T cell therapy up to 8 July 2022. Content: The epidemiology and outcomes of COVID-19 in patients with B-cell malignancy and CAR-T cell recipients are summarized. Vaccine efficacy in these subgroups is compiled. Considering the successive surges of variants of concern, we propose a critical appraisal of treatment strategies by discussing the use of neutralizing monoclonal antibodies, convalescent plasma therapy, direct-acting antiviral drugs, corticosteroids, and immunomodulators. Implications: For patients with B-cell malignancy, preventive vaccination against SARS-CoV-2 remains essential and the management of COVID-19 includes control of viral replication because of protracted SARS-CoV-2 shedding. Passive immunotherapy (monoclonal neutralizing antibody therapy and convalescent plasma therapy) and direct-active antivirals, such as remdesivir and nirmatrelvir/ritonavir are the best currently available treatments. Real-world data and subgroup analyses in larger trials are warranted to assess COVID-19 therapeutics in B-cell depleted populations.